NLRP14 deficiency causes female infertility with oocyte maturation defects and early embryonic arrest by impairing cytoplasmic UHRF1 abundance - Wenzhe Zhang; Rongrong Zhang; Ling Wu; Chendi Zhu; Chuanxin Zhang; Chengpeng Xu; Shidou Zhao; Xinchen Liu; Ting Guo; Yueshuang Lu; Zheng Gao; Xiao Yu; et al. (Cell Reports, 2023)
Summary: Oocyte maturation is vital to attain full competence required for fertilization and embryogenesis. NLRP14 is preferentially expressed in mammalian oocytes and early embryos. Yet, the role and molecular mechanism of NLRP14 in oocyte maturation and early embryogenesis are poorly understood, and whether NLRP14 deficiency accounts for human infertility is unknown. Here, we found that maternal loss of Nlrp14 resulted in sterility with oocyte maturation defects and early embryonic arrest (EEA). Nlrp14 ablation compromised oocyte competence due to impaired cytoplasmic and nuclear maturation. Importantly, we revealed that NLRP14 maintained cytoplasmic UHRF1 abundance by protecting it from proteasome-dependent degradation and anchoring it from nuclear translocation in the oocyte. Furthermore, we identified compound heterozygous NLRP14 variants in women affected by infertility with EEA, which interrupted the NLRP14-UHRF1 interaction and decreased UHRF1 levels. Our data demonstrate NLRP14 as a cytoplasm-specific regulator of UHRF1 during oocyte maturation, providing insights into genetic diagnosis for female infertility.